An Old Norse Image Hoard: From the Analog Past to the Digital Present - Baer, Patricia Ann (2013)
My Interdisciplinary dissertation examines illustrations in manuscripts and early print sources and reveals their participation in the transmission and reception of Old Norse mythology. My approach encompasses Material Philology and Media Specific Analysis. The reception history of illustrations of Old Norse Mythology affects our understanding of related Interdisciplinary fields such as Book History, Visual Studies, Literary Studies and Cultural Studies. Part One of my dissertation begins with a discussion of the tradition of Old Norse oral poetry in pagan Scandinavia and the highly visual nature of the poems. The oral tradition died out in Scandinavia but survived in Iceland and was preserved in vernacular manuscripts in the thirteenth century. The discovery of these manuscripts in the seventeenth century initiated a cycle of illustration that largely occurred outside of Iceland. Part One concludes with an analytical survey of illustrations of Old Norse mythology in print sources from 1554 to 1915 revealing important patterns of transmission. Part Two traces the technological history of production of digital editions and manuscript facsimiles back to the seventeenth century when manuscripts were hand-copied and published by means of copperplate engravings. Part Two also discusses the scholarly and cultural prejudices towards images that are only now slowly fading. Part Two concludes with a description of my prototype for a digital image repository named MyNDIR (My Norse Digital Image Repository). MyNDIR will facilitate the emergence of images of Old Norse Studies from the current informal crowd sourcing of material on the web to a digital image repository supporting the dissemination of accurate scholarly knowledge in a widely accessible form. Part Three presents two thematic case studies that demonstrate the value of applying the skills of visual literacy to illustrations of Old Norse mythology. The first study examines Jakob Sigurðsson’s illustrations of Norse gods in hand-copied paper manuscripts from ...